El mito de Sumpall en la cultura Mapuche - Carrasco, Hugo (Revista Chilena de Humanidades, 2016)
Prof. Carrasco’s contribution is concerned with a mythical figure of the Mapuche culture derived from his ethnographic research. Description and interpretation provided here draw from several research scholars whose opinion add up to the results of Prof. Carrasco’s field work, who exemplifies on the existence of this mythical being from two sources of legends about it, transcribed in Spanish and in the Mapudungu tongue.